Luminescence properties and site occupancy of Ce3+ in Ba2SiO4: a combined experimental and ab initio study. Issue 41 (12th May 2017) - Lin, Litian; Huang, Xiaoxiao; Shi, Rui; Zhou, Weijie; Huang, Yan; Zhong, Jiuping; Tao, Ye; Chen, Jun; Ning, Lixin; Liang, Hongbin
Abstract : Luminescence properties of Ce 3+ in Ba2 SiO4 were investigated by a combination of experimental and ab initio methods. Abstract : Photoluminescence properties of Ba2−2 x Ce x Na x SiO4 ( x = 0.0005) prepared by a solid-state reaction method are first studied with excitation energies in the vacuum-ultraviolet (VUV) to ultraviolet (UV) range at low temperature. Five bands are observed in the excitation spectrum of Ce 3+ 5d → 4f emission at 26.5 K. The highest energy band is attributed to the host excitonic absorption, from which the band gap energy of the host is estimated to be around 7.36 eV. The four lower energy bands are assigned to the 4f → 5d transitions of Ce 3+ located at one of the two types of Ba sites in Ba2 SiO4, based on a comparison of excitation spectra at different monitoring wavelengths. Under UV excitation, the material exhibits bright luminescence at 350–450 nm, with a fast decay time (∼26 ns at 4 K) and a high thermal quenching temperature (>500 K). In view of this, X-ray excited luminescence measurements are then conducted, and the results suggest a potential application of Ba2 SiO4 :Ce 3+ as scintillation phosphors. Hybrid density functional theory (DFT) calculations within the supercell model are carried out to optimize the local structures of Ce 3+ at the two Ba sites in Ba2 SiO4, on which wave function-based ab initio embedded cluster calculations are performed to derive the 4f 1 and 5d 1 energy levels of Ce 3+ . On the basis of the calculated DFT total energies and the comparison between experimental and calculated 4f → 5d transition energies, we find that the luminescence originates predominantly from Ce 3+ occupying nine-coordinated Ba2 sites. Furthermore, electronic properties of Ce 3+ in Ba2 SiO4 are evaluated to provide an understanding of the high thermal stability of the 5d luminescence at the level of electronic structures.